Corpectomy and expandable cage replacement versus third generation percutaneous augmentation system in case of vertebra plana: rationale and recommendations - Vanni, Daniele; Pantalone, Andrea; Magliani, Vincenzo; Salini, Vincenzo; Berjano, Pedro (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Background: To evaluate the role of third generation percutaneous vertebral augmentation systems (Spine Jack®) as alternative to the corpectomies and expandable cages replacement (X-Core® Adjustable VBR System) in the treatment of vertebra plana (VP) as complication of the osteoporosis vertebral fracture (OVF). Methods: Spine Jack® is a new device for mechanical kyphoplasty (MK). It is a titanium implant designed to restore the height of the vertebral body in OVF, primary or secondary bone tumors, or traumatic fractures. The X-Core® adjustable VBR System is a vertebral body replacement device indicated for use in the thoracolumbar spine (T1 to L5). The preoperative radiographic exams, computed tomography (CT), and magnetic resonance imaging (MRI) were performed in all cases. Clinical outcome measures included preoperative and postoperative Oswestry Disability Index (ODI), Visual Analog Scale pain score (VAS), neurologic examination, complications, estimated blood loss, and operating time. Postoperative radiographic evaluations were made at 1, 6, and 12 months. Results: The anterior and middle column reconstruction by Spine Jack represents a valid alternative to the corpectomy in the patients affected by VP, especially in case elderly and/or high operative risk. In case of Spine Jack use, the correct indications must be respected: the hyperintense signal in STIR MRI sequences to the level of the fractures must be present. The eventual posterior spinal cord compression represents a relative contraindication. In case it would be superior to 1/3 and 2/3 respectively in case of fractures level above and below the spinal cord, a direct posterior spinal cord decompression must be performed. Conclusions: Avoiding the corpectomy, it is possible to reduce the operating time and the associated risks, as well as reducing blood loss.